Analysis of Inclusive Education in the Christian Context - Henderina Bathun, Victoria; Manggoa, Melkias Antonias; Sairwona, Wellem; Rajaguguk, Wilson; Penturi, Thomas (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
Inclusive education is an approach that places all students, including those with special needs, in an equal and equitable education system. In the context of Christianity, inclusive education is not only a response to pedagogical needs, but also a manifestation of theological values such as love, justice, acceptance, and recognition of the dignity of every human being as the image and likeness of God (Imago Dei). This article analyzes inclusive education from a Christian perspective by reviewing the basic principles of inclusivity and pedagogy, the legal foundations, as well as those underlying its application. This research also reviews the role of churches and schools in forming inclusive educational communities, including in curriculum development, provision of infrastructure, and social-spiritual empowerment. The method used is a literature study of academic literature and biblical texts. The results of the study show that inclusive education in Christianity is not just a social obligation, but a deep call of faith to restore and embrace all of God's creation in its entirety. The Church and Christian educational institutions are required to be exemplary in building a humane and liberating education system.